ETIKA DAN HUKUM IMPLEMENTASI SISTEM INFORMASI MANAJEMEN SERTA DAMPAK TERHADAP MASALAH SOSIAL DAN BUDAYA ORGANISASI - FITRIANI FITRIANI (Adaara: Jurnal Manajemen Pendidikan Islam, 2017)
This paper describes about ethics and law in applying management information system. The development of technology through computers, internet and other hardware and software as a means of information provide positive impacts and negative impacts. Implementation of management information systems affect the social and cultural issues of the organization in the world of education. It takes ethics and law so that the negative impact of utilization of management information system can be minimized.